KONTRIBUSI DAYA TAHAN KEKUATAN DAN POWER OTOT TUNGKAI TERHADAP HASIL LARI SPRINT 100 METER PADA SISWA EKTRAKURIKULER SMP NEGERI 1 BALAI JAYA ROKAN HILIR - Anggraini, Sri Rahayu; Sulastio, Agus; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to determine the contribution of muscular enduranceand leg muscle power to the 100-meter sprint performance of extracurricular studentsat SMP Negeri 1 Balai Jaya Rokan Hilir. The research used the product momentcorrelation method. The population consisted of 18 male extracurricular students fromSMP Negeri 1 Balai Jaya, using a total sampling method. The instruments used weresquats, vertical jumps, and 100-meter sprints. Data analysis was performed usingmultiple correlation analysis. Based on the data analysis and discussion, the calculatedR value was 0.961, while the critical value (r table) at α = 0.05 was 0.521, indicatingthat the calculated R value > r table. This means there is a significant relationshipbetween muscular endurance and leg muscle power collectively on the 100-meter sprintperformance. To determine the contribution, the correlation coefficient (r) is squaredand multiplied by one hundred (r² x 100%). The statistical analysis results showed thatR = 0.961, meaning that muscular endurance and leg muscle power collectivelycontribute 92.35% to the 100-meter sprint performance.Keywords: Muscular Endurance, Leg Muscle Power, 100-meter Sprint